2022
DOI: 10.1126/science.abg5601
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of somatic noncoding mutation patterns in cancer

Abstract: We established a genome-wide compendium of somatic mutation events in 3949 whole cancer genomes representing 19 tumor types. Protein-coding events captured well-established drivers. Noncoding events near tissue-specific genes, such as ALB in the liver or KLK3 in the prostate, characterized localized passenger mutation patterns and may reflect tumor-cell-of-origin imprinting. Noncoding events in regulatory promoter and enhancer regions frequently involved cancer-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 211 publications
2
43
0
Order By: Relevance
“…A typical example of such driver genes is TERT , the gene for the telomerase reverse transcriptase. The coding-region of this gene shows no significant sign of selection [ 3 ], whereas its promoter is a target for driver mutations in many types of cancer [ 19 , 20 ]. It is noteworthy in this respect that recent studies have shown that the enhancer region of one of the cancer genes identified here, TNFSF10 , is subject to somatic mutation in kidney cancer [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…A typical example of such driver genes is TERT , the gene for the telomerase reverse transcriptase. The coding-region of this gene shows no significant sign of selection [ 3 ], whereas its promoter is a target for driver mutations in many types of cancer [ 19 , 20 ]. It is noteworthy in this respect that recent studies have shown that the enhancer region of one of the cancer genes identified here, TNFSF10 , is subject to somatic mutation in kidney cancer [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…These tests are based on determining an increased mutational frequency in DNA regions of interest (e.g., cis-regulatory elements (CREs)) compared to a background mutational frequency [10][11][12][13][14][15][16][17][18] . Methods have employed a range of different parameters to estimate the background mutational frequency in CREs, including cancer-specific mutational signatures, sequence conservation, functional annotations, mutational frequencies in neighboring regions or other "similar" genomic regions, replication timing, and expression levels 9,19 . Despite these varied approaches to estimate mutational burden and the increasing number of sequenced tumor samples, studies have only identified ~100 driver NCVs.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent analysis of 3,949 tumors from PCAWG and the Hartwig Medical Foundation identified driver NCVs in the promoters and enhancers of 52 genes 19 . Additional driver NCVs have been identified in the super-enhancers of BLC6, BCL2, CXCR4 in diffuse large B-cell lymphomas 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of low-penetrance risk variants have been identified over years but the effect sizes of such individual single-nucleotide polymorphisms (SNPs) are quite small 6 . Besides, given the fact that only 2% mutations are related to the protein-coding genome and non-coding regions may harbour driver genes 7 , to detect or elucidate cancer prognosis we clearly require more downstream information.…”
Section: Introductionmentioning
confidence: 99%